2007
DOI: 10.1007/s10589-007-9082-4
|View full text |Cite
|
Sign up to set email alerts
|

Kantorovich’s majorants principle for Newton’s method

Abstract: We prove Kantorovich's theorem on Newton's method using a convergence analysis which makes clear, with respect to Newton's Method, the relationship of the majorant function and the non-linear operator under consideration. This approach enable us to drop out the assumption of existence of a second root for the majorant function, still guaranteeing Q-quadratic convergence rate and to obtain a new estimate of this rate based on a directional derivative of the derivative of the majorant function. Moreover, the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
112
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 8 publications
7
112
0
Order By: Relevance
“…We present, under a weak majorant condition, a local convergence analysis for the Gauss-Newton method for injective-overdetermined systems of equations in a Hilbert space setting. Our results provide under the same information a larger radius of convergence and tighter error estimates on the distances involved than in earlier studies such us [10,11,13,14,18]. Special cases and numerical examples are also included in this study.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…We present, under a weak majorant condition, a local convergence analysis for the Gauss-Newton method for injective-overdetermined systems of equations in a Hilbert space setting. Our results provide under the same information a larger radius of convergence and tighter error estimates on the distances involved than in earlier studies such us [10,11,13,14,18]. Special cases and numerical examples are also included in this study.…”
supporting
confidence: 66%
“…It was shown that this condition is better that Wang's condition [18], [22] in some sense. A certain relationship between the majorant function and operator F was established that unifies two previously unrelated results pertaining to inexact Gauss-Newton methods, which are the result for analytical functions and the one for operators with Lipschitz derivative.similar improvements in both the local and semilocal case of the works in [10,11,13,12,22], have already been obtained by us in [3,4,5,6,7,9] under stronger than (2.2) majorant-type conditions. The paper is organized as follows: Section 2 contains the local convergence analysis of the Gauss-Newton method (1.2) under weak majorant conditions, whereas in Section 3 we provide special cases and numerical examples further validating the theoretical results.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations